Impact of Quorum Sensing Molecules on Plant Growth and Immune System - Shrestha, Abhishek; Grimm, Maja; Ojiro, Ichie; Krumwiede, Johannes; Schikora, Adam (Frontiers in Microbiology, 2020)
Bacterial quorum-sensing (QS) molecules are one of the primary means allowing communication between bacterial cells or populations. Plants also evolved to perceive and respond to those molecules. N-acyl homoserine lactones (AHL) are QS molecules, of which impact has been extensively studied in different plants. Most studies however, assessed the interactions in a bilateral manner, a nature of interactions, which occurs rarely, if at all, in nature. Here, we investigated how Arabidopsis thaliana responds to the presence of different single AHL molecules and their combinations. We assumed that this reflects the situation in the rhizosphere more accurately than the presence of a single AHL molecule. In order to assess those effects, we monitored the plant growth and defense responses as well as resistance to the plant pathogen Pseudomonas syringae pathovar tomato (Pst). Our results indicate that the complex interactions between multiple AHL and plants may have surprisingly similar outcomes. Individually, some of the AHL molecules positively influenced plant growth, while others induced the already known AHL-priming for induced resistance. Their combinations had a relatively low impact on the growth but seemed to induce resistance mechanisms. Very striking was the fact that all triple, the quadruple as well as the double combination(s) with long-chained AHL molecules increased the resistance to Pst. These findings indicate that induced resistance against plant pathogens could be one of the major outcomes of an AHL perception. Taken together, we present here the first study on how plants respond to the complexity of bacterial quorum sensing.